EVALUASI KEBUTUHAN AIR IRIGASI MENGGUNAKAN APLIKASI CROPWAT 8.0 STUDI KASUS DI DESA CARAWALI KABUPATEN SIDENRENG RAPPANG - Benny; Reza Asra; Rifni Nikmat Syarifuddin (Innofarm : Jurnal Inovasi Petanian, 2025)
Limited irrigation water availability is a challenge for sustainable agricultural management, especially in Carawali Village, Sidenreng Rappang Regency, one of South Sulawesi's rice production centers. This study aims to analyze irrigation water requirements for rice fields in the area using CROPWAT 8.0. The methodology involved collecting climatological data, rainfall records, crop type information, and soil characteristics, which were then analyzed quantitatively through CROPWAT simulations. The results show that the rice crop water requirement (CWR) during the planting season is 741.2 mm, with an effective rainfall of 547.2 mm, leaving a deficit of 435.5 mm. The highest irrigation needs occur in the third decade of September at 162.4 mm, namely in the early growth phase when rainfall is insufficient. Keywords: Carawali; CROPWAT 8.0; irrigation schedule; rice; Irrigation water requirements; Village